Dangerous subtlety: relationship-related determinants of consistency of condom use among female sex workers and their regular, non-commercial partners in Hai Phong, Viet Nam. - Hoffman, Leah; Nguyen, Ha Thi Thu; Kershaw, Trace S; Niccolai, Linda M (AIDS and behavior, 2011)
Research indicates female sex workers use condoms more consistently with their clients than with regular, non-commercial partners (partners). The purpose of this study was to better understand the relationship between couple communication and HIV risk behavior by examining (1) sex worker-partner divergence on communication measures and (2) the association between intra-couple communication divergence and consistent condom use. In this cross-sectional study, 50 sex workers and their partners in Hai Phong, Viet Nam were separately asked about their relationships and condom use. When asked about HIV risk communication in their relationship, sex workers reported significantly higher HIV communication content than their partners (p < 0.001). Higher communication divergence between partners was associated with a decreased likelihood of consistent condom use (OR 0.54 95% CI 0.30, 0.97). Sex workers urgently need interventions that build their communication skills and address their risk behavior in non-commercial relationships.
Keywords: Adult; Communication; Condoms; Cross-Sectional Studies; Female; HIV Infections; Humans; Prostitution; Questionnaires; Risk Factors; Risk-Taking; Sex Workers; Sexual Partners; Vietnam; Young Adult